2020
DOI: 10.1107/s1600577520006724
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of third-order nonlinear dynamical X-ray diffraction based on a new exact solution

Abstract: Third-order nonlinear two-wave dynamical X-ray diffraction in a crystal is considered. For the Laue symmetrical case of diffraction a new exact solution is obtained. The solution is presented via Jacobi elliptic functions. Two input free parameters are essential: the deviation parameter from the Bragg exact angle and the intensity of the incident wave. It is shown that the behavior of the field inside the crystal is determined by the sign of a certain combination of these parameters. For negative and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…( ) It was shown that in the third-order nonlinear symmetrical Laue case the Pendellösung effect also takes place [30,32]. Here we will show that the Pendellösung effect also takes place in the asymmetrical nonlinear case.…”
Section: Nonlinear Pendellösung Effectmentioning
confidence: 52%
See 2 more Smart Citations
“…( ) It was shown that in the third-order nonlinear symmetrical Laue case the Pendellösung effect also takes place [30,32]. Here we will show that the Pendellösung effect also takes place in the asymmetrical nonlinear case.…”
Section: Nonlinear Pendellösung Effectmentioning
confidence: 52%
“…The exact solutions for the third-order nonlinear symmetrical Laue diffraction in non-absorbing crystals have been found for forbidden 2h reflection and for an incident plane σ-polarized wave. The deviation from the Bragg exact orientation was set zero [30] and nonzero [32]. As in both cases, here also we will search the exact solution in the form r…”
Section: Exact Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extension of the linear dynamical diffraction Takagi's equations (Takagi, 1969) for the third-order nonlinear case has been obtained (Balyan, 2015a). The behaviour of the diffracted wavefields in the third-order nonlinear case on the basis of the exact solutions has been theoretically investigated for the symmetric Bragg case (Balyan, 2015b), for the symmetric Laue case (Balyan, 2016a(Balyan, , 2020 and for the asymmetric Laue case (Balyan, 2021). The third-order nonlinear dynamical diffraction of X-ray pulses has been theoretically investigated as well (Balyan, 2016b).…”
Section: Introductionmentioning
confidence: 99%